AlphaLISA for detection of staphylococcal enterotoxin B free from interference by protein A. (July 2019) - Zhao, Junqing; Lv, Qingyu; Liu, Peng; Guo, Liyuan; Zhang, Liwen; Zheng, Yuling; Ming, Lihua; Kong, Decong; Jiang, Hua; Jiang, Yongqiang
Abstract: Staphylococcal enterotoxin B (SEB) is an important enterotoxin which is a major reason for food poisoning and a potential biologic agent. Hence, rapid and accurate detection is very important. An amplified luminescent proximity homogeneous assay (AlphaLISA) for SEB detection was established here. Its performance was evaluated on mock specimen and culture supernatant. Its free from the effect of protein A was compared with ELISA. Results showed that the linear range for SEB detection was 25 pg/mL to 25 ng/mL. The detection limitation is 25 pg/mL in buffer and 50 pg/mL in specimen respectively. There was no cross-reaction with other classical SEs or botulinum toxin. AlphaLISA was also tolerant to the matrix of sample and showed good repeatability. The inter-assay coefficient of variation (CV) and intra-assay CV were<10% for buffer and mock specimens, respectively. Besides AlphaLISA detection was free of the interference of protein A (which is the obstacle for immune-based detection of SEs in Staphylococcus aureus culture supernatants): this feature is very important for food-poisoning confirmation caused by SEB contamination. These data suggest that the AlphaLISA established here is well suited for SEB detection in food samples and S. aureus culture supernatants. Highlights: AlphaLISA is sensitive, specific and rapid for SEB detection. For food sample detection, AlphaLISA could withstand the influence of matrix. For S. aureus supernatant detection, AlphaLISA overcomes the hindrance of protein A.